FIRST TURJAITE FIND ON OCEANIC ISLANDS - Kogarko L.N.; Karpenko S.F.; Frikh-Khar D.I. (My University, 1989)
Studying the alkalic igneous activity of ocean islands is a problem that should be solved in the context of reconstructing the geodynamic regime of the oceanic lithosphere, as well as the geochemical evolution and heterogeneity of the Earth's upper mantle. We thought that it would be very interesting to compare the alkalic igneous activity of oceanic islands and continental rift systems, where there are thick bodies of igneous rocks relatively high in alkalies. As a result of the geologic expedition to the Cape Verde Islands, we were able to find and study an intrusive complex of alkalic rocks, including melilite-bearing varieties that were hitherto known only in continental ultramafic-alkalic rock associations. Our study of intrusive turjaite found for the first time on oceanic islands and analogous to continental melilite-bearing rocks indicates the similarity between the geologic and geochemical conditions of ultramafic-alkalic igneous activity on the continents and in the oceans.